Analisis Yuridis Pengguna Jasa Ekspedisi Terhadap Barang Kiriman yang Tidak Dapat Dikeluarkan Petugas Bea dan Cukai di Free Trade Zone - R. Tria Flamitha; Fadlan Fadlan; Christiani Prasetiasari; Erniyanti Erniyanti (Jurnal Studi Multidisiplin Ilmu, 2023)
Purpose: The aim of this research is to find out the legal regulations for users of expedition services for goods that cannot be released by customs and excise officers in the Free Trade Zone (FTZ) area, and how they are implemented, obstacle factors and efforts of users of expedition services for goods. Research methodology: The research method for this thesis is normative juridical (legal research) through literature study with an empirical juridical approach (sociological juridical) through field studies aimed at gaining legal knowledge empirically. Results: The research results show that legal regulations for expedition service users in the case of goods that cannot be released by Customs and Excise officers in the Free Trade Zone (FTZ) area are regulated based on Article 16 of Law Number 17 of 2006 concerning Customs and also Article 20 paragraph ( 1) Regulation of the Minister of Finance of the Republic of Indonesia Number: 199 /PMK.Ol0/2019 concerning Customs, Excise and Tax Provisions for the Import of Shipped Goods, which regulates actions to detain shipped goods that do not pay the customs tariff and value as determined. Limitation: Implementation of expedition service users for goods that cannot be released by Customs and Excise officers in the Free Trade Zone (FTZ) area, as observed at PT. Batam Branch Logistics Trade Ambassador, demonstrated the complexity involving laws, procedures and economic challenges Contribution: This research highlights the importance of understanding the legal regulations governing the detention of goods in the FTZ area and the challenges faced by users of expedition services in complying with these regulations.